Nitrogen rates and plant density interactions enhance radiation interception, yield, and nitrogen use efficiencies of maize - Tian, Peiyu; Liu, Jiamin; Zhao, Yanan; Huang, Yufang; Lian, Yanhao; Wang, Yang; Ye, Youliang (Frontiers in Plant Science, 2022)
The contributions of different leaf layers to maize yields have been identified as middle leaf > lower leaf > upper leaf, where the vertical photosynthetically active radiation (PAR) in the canopy gradually decreases. We hypothesized that the allocation of more PAR and nitrogen (N) to concentrate on the highest contributing leaves will be beneficial for higher yields and N use efficiencies. N application rate and plant density effectively regulated the canopy light and N distribution. We evaluated the interactive effects of the N rate and plant density on the agronomic and ecophysiological characteristics of leaves at different orientations in a 2019/2020 field experiment. In this study, an N application rate of 180 kg ha-1 coupled with a plant density of 82500 plants ha–1 achieved the highest yield and N recovery efficiency (NRE). In contrast to traditional farming practices in Northern China, the density was increased, and the N rate was reduced. A densification of from 52500 to 82500 plants ha-1 increased the population leaf area index (LAI) by 37.1% and PAR by 28.4%; however, an excessive density (from 82500 to 97500 plants ha-1) drastically reduced the proportion of PAR by 28.0% in the lower leaves. With increased density, the leaf areas and angles of the upper leaves decreased much more than the other leaves, which allowed the middle and lower leaves to access more light, which manifested a smaller extinction coefficient for light (KL). The high yield (>1000 kg ha-1) of maize could be achieved simultaneously with higher NRE; however, it was negatively correlated with the internal N use efficiency (IEN). Higher N concentrations and a lower total performance index (PItotal) in the lower leaves might be an important rationale for the reduction of IEN in high-yielding maize. Additionally, the decreased N rate without yield reduction under higher densities was primarily attributed to the vertical N distribution being more uniform (a smaller extinction coefficient for N (KN)). These results suggested that the N fertilizer rate can be moderately reduced without the reduction of maize yields under high plant densities in Northern China.